(DFT)دراسة ذرة الهيدروجين بإستعمال نظرية تابعي الكثافة - بوساحة, رميسة (جامعة الوادي University of Eloued, 2019)
"ملخص تهدف هذه المذكرة إلى دراسة ذرة الهيدروجين بإستعمال نظرية تابعي الكثافة أي بتطبيق هذا التابعي على ذرة الهيدروجين . حيث قمنا أولا بإيجاد دالة الموجة الذرة الهيدروجين التي تحتوي على إلكترون واحد حيث تمكننا من حساب الطاقة لهذه الذرة بواسطة حل معادلة شرودينغر . وكذالك توصلنا بإستعمال تقريب تابعي الكثافة حل معادلة شرودينغر للذرات المتعددة الإلكترونات فعند تطبيقنا لهذه النظرية الذرة الهيدروجين كان سئ بسبب هذه النظرية تختص بالذرات المتعددة الإلكترونات وليس بذرة أحادية الإلكترون أي أن الإختلاف يكمن في طاقة الترابط والتبادل. ""Abstract This research aims to study hydrogen atom by Using density functional theory.In otherwords, by applying atom functional hydrogen. Firstly, we have found wave functional atomhydrogen which includes one electron as result we have calculated energy to this atom by doingchorodingor equation.In addition to that, we have used approximation functional density theoryfor doing chorodingor equation to multi electron atom. Consequently, this application was bad because this theory specialized for multi electron atomnot for mono electron.That is to say,that the difference is in exchange correlation energy "
مذكرة ماستر تخصص فيزياء
Keywords: ذرات متعددة الالكترونات- ذرة الهيدروجين- نظرية تابعي الكثافة; density functional theory-multi electron atom